A systematic study of the structure–property relationship of a series of nonlinear optical (NLO) julolidinyl-based chromophores with a thieno[3, 2-b]thiophene moiety. Issue 2 (20th November 2014) - Zhang, Airui; Xiao, Hongyan; Cong, Shengyu; Zhang, Maolin; Zhang, Hua; Bo, Shuhui; Wang, Qi; Zhen, Zhen; Liu, Xinhou
Abstract : A series of NLO chromophoresa–d bearing thieno[3, 2- b ]thiophene (TT) as the conjugated bridge or the lateral moiety have been synthesized and investigated. Abstract : A series of nonlinear optical (NLO) chromophoresa–d bearing thieno[3, 2- b ]thiophene (TT) as the conjugated bridge or the lateral moiety have been synthesized and investigated. These chromophores display the same julolidinyl-based electron donor, but different electron acceptors ( i.e., 2-dicyanomethylene-3-cyano-4-methyl-2, 5-dihydrofuran, TCF, or malononitrile). The solvatochromic behavior, thermal stability and electrochemical properties were evaluated to study the structure–property relationships. The solvent dependence of dipole moment ( μ ), static polarizability ( α ), hyperpolarizability ( β ) and bond length alternation (BLA) of all chromophores was demonstrated by density functional theory (DFT) calculations. Upon using the D–A–π–A structure, the blue-shifted phenomenon and substantially enhanced microscopic NLO properties of chromophored were obtained. The electrooptic coefficient ( r 33 ) of chromophorea (94 pm V −1 at 1.31 μm) was four times higher than that of chromophoreb (∼20 pm V −1 ), while the calculated hyperpolarizability ( β ) of chromophoreb was five times larger with respect to chromophorea . All the results demonstrated that the TT unit is a highly efficient conjugated bridge, and it has some electronical and sterical effects on macroscopic electrooptic (EO) activity when it is used as the lateral moiety. Guidelines can be proposed for the design of a new series of guest–host polymers including julolidinyl-based chromophores with a TT moiety, which could be useful in organic EO device fabrication.